Defects reduction of Ge epitaxial film in a germanium-on-insulator wafer by annealing in oxygen ambient - Lee, Kwang Hong (2015)
A method to remove the misfit dislocations and reduce the threading dislocations density (TDD) in the germanium (Ge) epilayer growth on a silicon (Si) substrate is presented. The Ge epitaxial film is grown directly on the Si (001) donor wafer using a “three-step growth” approach in a reduced pressure chemical vapour deposition. The Ge epilayer is then bonded and transferred to another Si (001) handle wafer to form a germanium-on-insulator (GOI) substrate. The misfit dislocations, which are initially hidden along the Ge/Si interface, are now accessible from the top surface. These misfit dislocations are then removed by annealing the GOI substrate. After the annealing, the TDD of the Ge epilayer can be reduced by at least two orders of magnitude to <5 × 106 cm−2.